Leuko-antosianienbinders as beheermaatreël vir die voorkoming van bruinwording in Protealoofblare - Du Plessis, Dawid Gerhardus Cornelius (2014)
M.Sc. (Botany) === The purpose of this investigation was to determine the effects of various physical treatments (limitation of transpiring surface, removal of stem base and changing of vase water and different numbers of inflorescence per constant volume of vase water) on the browning of foliage and the rate of water absorption by Protea neriifolia in florescences. The binding capacity of lead acetate with flavonoids in vase media was also determined. The limitation of the number of leaves (transpiring surface) per peduncle resulted in less absorption of leached browning and stem plugging components. Regular removal of the stem base and changing of vase water inhibit stern blockage and accumulation of leached products in the vase medium. A large number of inflorescences in a limited volume of vase medium resulted in higher concentrations of leached flavonoids and other browning components. A reduced number of leaves per peduncle, regular removal of stern base and changing of vase water, as well as a limited number of inflorescences per constant volume of vase medium, ensured adequate continuous water uptake, which is essential to limit browning.